2010
DOI: 10.1103/physrevd.81.103514
|View full text |Cite
|
Sign up to set email alerts
|

On the dark sector interactions

Abstract: It is possible that there exist some interactions between dark energy (DE) and dark matter (DM), and a suitable interaction can alleviate the coincidence problem. Several phenomenological interacting forms are proposed and are fitted with observations in the literature. In this paper we investigate the possible interaction in a way independent of specific interacting forms by use of observational data (SNe, BAO, CMB and Hubble parameter). We divide the whole range of redshift into a few bins and set the intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
199
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(219 citation statements)
references
References 61 publications
(54 reference statements)
16
199
4
Order By: Relevance
“…The assumed form will lead to a bias when observational data are used to give the constraint on the interaction. In [11] the authors investigated the possible interaction in a way independent of specific interacting forms by dividing the whole range of * Electronic address: yangtao@itp.ac.cn † Electronic address: guozk@itp.ac.cn ‡ Electronic address: cairg@itp.ac.cn redshift into a few bins and setting the interacting term to be a constant in each redshift bin. It was found that the interaction is likely to cross the noninteracting line and has an oscillation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumed form will lead to a bias when observational data are used to give the constraint on the interaction. In [11] the authors investigated the possible interaction in a way independent of specific interacting forms by dividing the whole range of * Electronic address: yangtao@itp.ac.cn † Electronic address: guozk@itp.ac.cn ‡ Electronic address: cairg@itp.ac.cn redshift into a few bins and setting the interacting term to be a constant in each redshift bin. It was found that the interaction is likely to cross the noninteracting line and has an oscillation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to alleviate the coincidence problem, an interaction between dark energy and dark matter has been considered extensively in the literature, for example, in [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and references therein. However, usually the interaction form has to be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case for [39] this is a result and not an objective, but in his case it was obtained from observational modelling and not from a theoretical proposal. In addition, for the cases when it was a given sign change interaction, contrast with late Universe observational data has been done for [40] and [41].…”
Section: Interacting Fluids and Q-functionmentioning
confidence: 99%
“…There are few number of papers of change of sign for Q in the literature, [39], without choosing a special form of interaction Q, proposed a new approach in which such interaction is partitioned Q = 3Hδ(z) in the whole redshift range and δ(z) is constant in each partition. Fitting with observational data they found that the functional δ probably crosses the non-interacting line (δ(z) = 0).…”
Section: Interacting Fluids and Q-functionmentioning
confidence: 99%
“…Moreover, it was found that observations also support the phenemonon of decaying of CDM into DE (Pereira and Jesus 2009;Guo, et al 2007;Costa, et al 2009). Cai and Su (2010) fitted the interaction term ∆ with observations without choosing any specific form of it. They found that ∆ crosses the non-interacting line (∆ = 0) and changes its sign around z = 0.5.…”
Section: Equation Of State Parametermentioning
confidence: 99%